Quantificação dos Coeficientes de Transmissão Térmica Lineares. Pontes Térmicas - João Luís Barroso Barbosa Castro (2010)
The Regulation of the Characteristics of Thermal Performance of Buildings (RCCTE in Portuguese), approved by the Decree-Law 80/2006, defines the calculation method of energy loss by linear thermal bridges through the envelope of a building in Portugal, by establishing values for the linear thermal transmittance coefficients.This method has proved to be imprecise, providing, in general, conservative values that differ from the ones considered as reference, i.e., from the values that occur from the application of ISO 10211:2007 standard, which regulates the calculation of the linear thermal transmittance coefficients.In this dissertation, the calculation method of the ISO 10211:2007 standard is analyzed, as well as the calculation methods proposed by the Portuguese, Spanish and French regulations.In addition, two comparative analyses are made between the calculation methods of the three countries: first, the values of the linear thermal bridges on the RCCTE are directly compared with thevalues from the French and Spanish regulations; after, the three methods are applied to six real cases, allowing to observe the influence of the differences between the methods into the overall calculation of the buildings.After verifying the low accuracy of the Portuguese method on the analyses that were made, a new calculation method of easy application is purposed, which is more accurate than the current method, suggesting its consideration at the next RCCTE review. The French calculation method was used as a reference for the development of the proposed method, after confirming its accuracy regarding the ISO 10211:2007 standard.Finally, the proposed method is applied to the cases previously considered, both for the different configurations of linear thermal bridges on the RCCTE, as for the real examples considered before,confirming the improvement in precision comparatively to the method of the actual RCCTE.KEYWORDS: RCCTE, thermal bridges, psi, calculation method, validation.